Investigating the Feasibility of Urumia Urban Areas Livability using RALSPI Model - Farzaneh Sasanpour; Sara Alizadeh; Hourieh Aarabi Moghadam (تحقیقات کاربردی علوم جغرافیایی)
Livability approach is defined as the healthy, safe, suitable and economically accessible urban system that brings about high life quality and is considered as a subset of sustainable development. Although investigating urban livability can be advantageous in identifying deficiencies and taking actions in order to improve livability of the living environment of residents, but unfortunately there has been inadequate considerations about livability theory in Iran. the result, in this study, the livability of Urumia city has been investigated. Firstly, after devising 24 factors in 4 aspects (Physical-Environmental, Economic, Social and Health) this index was evaluated in urban areas by using newly invented model RALSPI with descriptive-analytical approach. Finally, based on this model, the areas were placed within the range of very livable to intolerable, so that District #1 was determined as the best area with livability score of 0.31 and District #2 was determined as the most unlivable area with the score of 0.007. This issue revealed a huge gap between the areas of the city.